Supramolecular Self‐Assembly as a Tool To Preserve the Electronic Purity of Perylene Diimide Chromophores. Issue 12 (8th February 2023) - Heckelmann, Ina; Lu, Zifei; Prentice, Joseph C. A.; Auras, Florian; Ronson, Tanya K.; Friend, Richard H.; Nitschke, Jonathan R.; Feldmann, Sascha
Abstract: Organic semiconductors are promising for efficient, printable optoelectronics. However, strong excited‐state quenching due to uncontrolled aggregation limits their use in devices. We report on the self‐assembly of a supramolecular pseudo‐cube formed from six perylene diimides (PDIs). The rigid, shape‐persistent cage sets the distance and orientation of the PDIs and suppresses intramolecular rotations and vibrations, leading to non‐aggregated, monomer‐like properties in solution and the solid state, in contrast to the fast fluorescence quenching in the free ligand. The stabilized excited state and electronic purity in the cage enables the observation of delayed fluorescence due to a bright excited multimer, acting as excited‐state reservoir in a rare case of benign inter‐chromophore interactions in the cage. We show that self‐assembly provides a powerful tool for retaining and controlling the electronic properties of chromophores, and to bring molecular electronics devices within reach. Abstract : Analysis of the photophysics of a supramolecular pseudo‐cube formed from perylene diimide (PDI) chromophores shows that, in contrast to the rapid excited‐state quenching observed upon uncontrolled aggregation of chromophores, the shape‐persistent cage retains the electronic purity of the PDIs. This allows delayed fluorescence arising from an excited multimer to be observed and showcases molecular self‐assembly as a powerful tool in organic electronics.